Measurement of Length of Hyperdense MCA Sign in Acute Ischemic Stroke Predicts Disappearance after IV tPA. Issue 1 (14th January 2013) - Shobha, Nandavar; Bal, Simerpreet; Boyko, Matthew; Kroshus, Eric; Menon, Bijoy K.; Bhatia, Rohit; Sohn, Sung‐Il; Kumarpillai, Gopukumar; Kosior, Jayme; Hill, Michael D.; Demchuk, Andrew M.
ABSTRACT BACKGROUND We sought to assess the hypothesis that length and volumes of middle cerebral artery (MCA) thrombus were associated with disappearance of the hyperdense middle cerebral artery sign (HMCAS) in acute ischemic stroke. METHODS This is a retrospective cohort study of acute ischemic stroke patients with MCA occlusion admitted to the University Hospital in Canada. The length and volumes of the HMCAS was measured on the plain CT by placing CTA images (CTA source images or MIP images) side‐by‐side. RESULTS Seventy‐six patients with acute stroke having HMCAS on noncontrast CT (NCCT) with M1 MCA occlusion confirmed by CT angiography or digital subtraction angiography and received tPA. The treatments received were: IV tPA 41(53.9%) and endovascular treatment ± IV tPA 35 (46.1%). In the IV tPA group, the rate of disappearance varied depending on the baseline HMCAS length. Short length HMCAS (<10 mm) disappeared in 6/7 (85.7%) (P < .001). Medium length HMCAS (10‐20 mm) disappeared in 9/24 (37.5%). No cases of long length HMCAS (>20 mm) disappeared (0/10) (P = .05). Rate of disappearance of HMCAS was found to be volume dependent (P < .002). CONCLUSION HMCAS length >10 mm infrequently disappears with IV tPA suggesting a potential need for ancillary therapy in this group.